2011
DOI: 10.1016/j.ccr.2011.08.024
|View full text |Cite
|
Sign up to set email alerts
|

An Antioxidant Response Phenotype Shared between Hereditary and Sporadic Type 2 Papillary Renal Cell Carcinoma

Abstract: Fumarate hydratase (FH) mutation causes hereditary type 2 papillary renal cell carcinoma (PRCC2). The main effect of FH mutation is fumarate accumulation. The current paradigm posits that the main consequence of fumarate accumulation is HIF-α stabilization. Paradoxically, FH mutation differs from other HIF-α stabilizing mutations, such as VHL and SDH mutations, in its associated tumor types. We identified that fumarate can directly up-regulate antioxidant response element (ARE)-controlled genes. We demonstrate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
315
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 358 publications
(328 citation statements)
references
References 62 publications
10
315
1
1
Order By: Relevance
“…Collectively, these findings support the notion that AA is capable of functioning as a signaling molecule in regulating muscle cell function. Interestingly, recent reports have demonstrated that abnormally accumulated fumarate plays a novel role in the irregular modification of cellular proteins (succination of KEAP1) and Nrf2 (NFE2-related factor 2) signaling in fumarate hydratase-deficient cells and that these functions are independent of its ability to inhibit ␣-ketoglutarate-dependent dioxygenases (17,(73)(74)(75). Thus, our findings and the results of prior studies collectively indicate that AA could regulate cellular activity independent of its energetic role.…”
Section: Discussionsupporting
confidence: 71%
“…Collectively, these findings support the notion that AA is capable of functioning as a signaling molecule in regulating muscle cell function. Interestingly, recent reports have demonstrated that abnormally accumulated fumarate plays a novel role in the irregular modification of cellular proteins (succination of KEAP1) and Nrf2 (NFE2-related factor 2) signaling in fumarate hydratase-deficient cells and that these functions are independent of its ability to inhibit ␣-ketoglutarate-dependent dioxygenases (17,(73)(74)(75). Thus, our findings and the results of prior studies collectively indicate that AA could regulate cellular activity independent of its energetic role.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we found that the NRF2 signaling pathway was the single most significantly dysregulated pathway in leiomyomas of the FH subtype, whereas the HIF1α signaling pathway was not significantly altered. We detected AKR1B10, a known target of NRF2 (29), as a highly promising biomarker for FH deficiency. NRF2 activation has previously been shown to redirect glucose and glutamine into anabolic pathways, including the pentose phosphate pathway (31).…”
Section: Discussionmentioning
confidence: 97%
“…The NRF2-mediated oxidative stress response was the most significantly dysregulated pathway in leiomyomas of the FH subtype (Table S1). Furthermore, 8 of the 20 most uniquely expressed genes (AKR1B10, TKT, PIR, SLC7A11, NQO1, SRXN1, SLC6A6, and GCLM) have previously been reported as targets of the transcription factor nuclear factor erythroid 2-related factor 2 (NRF2) (28)(29)(30)(31). The pentose phosphate pathway was the only other statistically significant pathway, and three (TKT, PGD, and G6PD) of the 20 most uniquely expressed genes encode for key enzymes of this pathway.…”
Section: Unsupervised Hierarchical Clustering Reveals Distinct Expresmentioning
confidence: 99%
“…In parallel to succinate, fumarate has been shown to competitively inhibit αKG‐dependent dioxygenase enzymes, resulting in a pseudohypoxic transcriptome through HIFα stabilization76 and a hypermethylator phenotype 76, 77. However, contrary to initial thoughts, now there is evidence to suggest that stabilization of HIF is not the driver of tumorigenesis in FH‐deficient tumors, and that a different candidate transcription factor—the nuclear‐related factor 2 (NRF2) pathway—may instead be involved 78, 79…”
Section: Mutations Of Mitochondrial (And Associated) Metabolic Enzymementioning
confidence: 99%